2020
DOI: 10.1186/s12889-020-08799-y
|View full text |Cite
|
Sign up to set email alerts
|

How does the two-child policy affect the sex ratio at birth in China? A cross-sectional study

Abstract: Background The One-Child Policy led to the imbalance of the sex ratio at birth (SRB) in China. After that, Two-Child Policy was introduced and gradually liberalized at three stages. If both the husband and wife of one couple were the only child of their parents, they were allowed to have two children in policy (BTCP). If only one of them was the only child, they were allowed to have two children in policy (OTCP). The Universal Two-Child Policy (UTCP) allowed every couple to have two children. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 56 publications
(88 reference statements)
1
27
0
Order By: Relevance
“…A universal decline can be observed over the years. With the universal two-child policy, the SRB has declined and approached the normal level, 46 but the difference by fertility policy area still existed.…”
Section: Resultsmentioning
confidence: 99%
“…A universal decline can be observed over the years. With the universal two-child policy, the SRB has declined and approached the normal level, 46 but the difference by fertility policy area still existed.…”
Section: Resultsmentioning
confidence: 99%
“…In China, pharmacists aged from 31 to 50 comprise the backbone of the department, and there was a higher demand for their professional knowledge. In addition, due to China's gradually open two child policy, the percentage of multiparous mothers and parturients who were≥30 years old rose significantly 21 , a considerable number of people in this age group have children at home, usually young children or infants, which are vulnerable to infection 22 , so there was a positive need for protection. In the designated hospital for treatment of COVID-19 patients, the drug supply center and inpatient pharmacy needed to know the information of therapeutic drugs for COVID-19 in advance to ensure the drug supply.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationship between universal two-child policy and newborn outcomes births is still unclear. Studies have reported that the change of the birth control policy might result in nationwide changes to a range of health outcomes, such as a more equal sex ratio, reduced neonatal mortality, 13 and increased risk of birth defects. 14 However, the new two-child policy might also be associated with outcomes related to birth term.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies showed that the relationship of universal two-child policy with obstetric issues can vary across different maternal characteristics. 13 16 24 For example, it has been reported that the associations between the two-child policy and sex ratios differed by maternal age, parity, and history of C-section. 13 It has also been found that the association of two-child policy with caesarean birth rate varies between nulliparous and multiparous women.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation